2020
DOI: 10.1080/09585192.2020.1841816
|View full text |Cite
|
Sign up to set email alerts
|

Breaking away or holding on to the past? Exploring HRM systems of export-oriented SMEs in a highly uncertain context: insights from a transition economy in the periphery

Abstract: Makhmadshoev D & Laaser K (2020) Breaking away or holding on to the past? Exploring HRM systems of export-oriented SME in a highly uncertain context: insights from a transition economy in the periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Issues regarding personnel risk (human resource management practices) in an organization stem from the nonexistence of specialized and competent workers (Bakos & Dănut, 2021;Makhmadshoev & Laaser, 2022), the nonexistence of practical training (Leonidou, 2004), the nonexistence of the determination of job tasks in firms, the existence of working disputes among employees (Catanzaro & Teyssier, 2021) and high employee turnover in an organization (Kotaskova et al, 2020). Exporting SMEs have also encountered these problems: exceptionally high employee turnover and worker disputes have made skilled employees migrate to other countries (Makhmadshoev & Laaser, 2022). Similarly, Mendy and Rahman (2019) have confirmed the negative impacts of language, the shortage of skilled labour, and training activities on the internationalization of SMEs.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues regarding personnel risk (human resource management practices) in an organization stem from the nonexistence of specialized and competent workers (Bakos & Dănut, 2021;Makhmadshoev & Laaser, 2022), the nonexistence of practical training (Leonidou, 2004), the nonexistence of the determination of job tasks in firms, the existence of working disputes among employees (Catanzaro & Teyssier, 2021) and high employee turnover in an organization (Kotaskova et al, 2020). Exporting SMEs have also encountered these problems: exceptionally high employee turnover and worker disputes have made skilled employees migrate to other countries (Makhmadshoev & Laaser, 2022). Similarly, Mendy and Rahman (2019) have confirmed the negative impacts of language, the shortage of skilled labour, and training activities on the internationalization of SMEs.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Some firms also develop their workers' abilities through work shadowing, enabling new employees working with experienced workers to learn business processes. Firms providing reward and incentive systems can also motivate their workers and increase the performance of employees (Makhmadshoev & Laaser, 2022). Moreover, firms developing their workers' abilities (Hamzah et al, 2022) and having an international human resource profile improve their success and competitiveness (Lozano-Torró et al, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The authors argue that employers need to develop very specific human resource practices to help employees cope with the uncertainties associated with the economic, social and cultural contexts. Makhmadshoev and Laaser's (2021) paper, set in the highly uncertain context of the post-socialist economy of Kyrgyzstan, highlights the challenges for small-and-medium-sized enterprises (SMEs) in supporting their workers through the uncertainties caused by the transition from a socialist to a capitalist economy. The study found that SMEs typically deployed one of the two, emergent, HR strategies that centre on the notion of path-dependence, with the aim of enabling workers to gain a sense of continuity while adapting to the new market-led system.…”
Section: Emerging Issuesmentioning
confidence: 99%